Deep Integration, Global Firms, and Technology Spillovers - Jinji, Naoto; Zhang, Xingyuan; Haruna, Shoji; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This open access book explores the impact of deep regional economic integration on spillovers of knowledge and technology across countries. Deep integration through signing deep regional trade agreements (DRTAs), which cover various policy areas in addition to tariff reductions, may or may not facilitate technology spillovers among their signatories. To understand the mechanism of the impact of deep integration on technology spillovers, this book starts by analyzing the behavior of global firms. Factors that affect global firms$1 (Bactivities, such as export, foreign direct investment (FDI), offshore outsourcing, are examined. Micro data on Japanese firms are employed for the analysis. Then, the relationships between bilateral trade patterns and technology spillovers and between types of FDI and technology spillovers are investigated in detail. Patent citation data are used to measure technology spillovers. Finally, the impact of DRTAs on international technology spillovers is analyzed. This book is highly recommended to readers who are interested in the effects of deep regional integration, including academic scholars, policymakers, and graduate students.s
Preface -- About the Authors -- Chapter 1 Introduction and Overview -- Chapter 2 The Trend of Deep Regional Integration -- Chapter 3 Which Aspect of Firm Performance is Important for the Choice of Globalization Mode?.-Chapter 4 Does Tobin$1 (Bs q Matter for a Firm$1 (Bs Choice of Globalization Mode? -- Chapter 5 Trade Patterns and International Technology Spillovers: Theory and Evidence from Japanese and European Patent Citations -- Chapter 6 Vertical versus Horizontal Foreign Direct Investment and Technology Spillovers -- Chapter 7 Do Deep Regional Trade Agreements Enhance International Technology Spillovers? Depth, Breadth, and Heterogeneity -- Chapter 8 Conclusion and Policy Implications -- References.s
Keywords: International economic relations; Economic history; Economics; International Economics; Economy-wide Country Studies; Economics